(3GdEJUGd GdaYGd aj EOGQI GdCYeGds - (3NVjQ cGXe(B, (3MehOs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3eaghe h WHjYI GdGJUGd , , THcGJ GdGJUGd ,GdGJUGd Hjf GdKbGaGJ GdeNJdaI , aGYdjI GdGJUGd Hjf GdGaQGO , egGQGJ GdGSJeGY , egGQGJ GdcJGHI h GdbQGAI , GdebGHdGJ GdTNUjI , GOGQI GdGLJeGYGJ , GOGQI GdeDJeQGJ , GYOGO h JMdjd GdJbGQjQ GdGOGQjI h GdeGdjI , JWhQ hSGFd GdGJUGds
(3eQGLY U(B.269s
Keywords: (3EOGQI GdCYeGds; (3GdGJUGd GdLeGgjQjs; (3GdGJUGdGJ GdGOGQjIs